2012
DOI: 10.1128/jvi.00015-12
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Cytomegalovirus in Malignant Gliomas

Abstract: Human cytomegalovirus (HCMV) has been found in malignant gliomas at variable frequencies with efforts to date focused on characterizing the role(s) of single gene products in disease. Here, we reexamined the HCMV prevalence in malignant gliomas using different methods and began to dissect the genetics of HCMV in tumors. HCMV DNA was found in 16/17 (94%) tumor specimens. Viral DNA copy numbers were found to be low and variable, ranging from 10 2 to 10 6 copies/500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 59 publications
5
77
1
Order By: Relevance
“…26 Other studies have suggested that halted differentiation of neuroprogenitor cells is an early step in gliomagenesis. 27 Since HCMV proteins and nucleotide sequences seem to be present in most GBMs 16,[28][29][30] and that HCMV-IE expression is a prognostic marker for poor patient survival irrespective of the GBM subtype, 18 our present model of HCMV infection of primary GBM cells appears to recapitulate early events during glioma development.…”
Section: Discussionmentioning
confidence: 90%
“…26 Other studies have suggested that halted differentiation of neuroprogenitor cells is an early step in gliomagenesis. 27 Since HCMV proteins and nucleotide sequences seem to be present in most GBMs 16,[28][29][30] and that HCMV-IE expression is a prognostic marker for poor patient survival irrespective of the GBM subtype, 18 our present model of HCMV infection of primary GBM cells appears to recapitulate early events during glioma development.…”
Section: Discussionmentioning
confidence: 90%
“…Forty-seven of the 48 samples were collected from infants with congenital CMV infection, and 1 sample was collected from an adult with glioblastoma multiforme (GBM). The GBM sample has been described previously (16) and was included to serve as an outlier to compare with the remaining samples. The dataset encompasses over 41 gigabases of HCMV sequence (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Subjects B101, B103, M103, MS1, and MS2 were described previously (11) as were U01, U04, and U33 (10) and G1 (16). The use of specimens from subjects PL2 and U45 was approved by the University of The samples H5478/H5529 and H1109/H1861/H1875 were derived from the Epidemiologische Untersuchung zur Erhebung der lnzidenz der kongenitalen Cytomegalvirus Infektion study, which was approved by the EthikKommission der Medizinischen Fakultät at the Universitätsklinikum Tübingen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 This phenomenon has been reported by other groups as well. 18,19 Studies using PCR techniques to detect 20 different regions of the CMV genome found CMV positivity was much more likely in GBM samples compared to epilepsy samples. 20 They also found that CMV detection was higher in more recent samples compared to older samples.…”
Section: Detection In Gliomasmentioning
confidence: 99%